2014
DOI: 10.1186/1471-2334-14-95
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and types of rectal douches used for anal intercourse: results from an international survey

Abstract: BackgroundRectal products used with anal intercourse (AI) may facilitate transmission of STIs/HIV. However, there is limited data on rectal douching behavior in populations practicing AI. We examined the content, types of products, rectal douching practices and risk behaviors among those reporting AI.MethodsFrom August 2011 to May 2012, 1,725 women and men reporting receptive AI in the past 3 months completed an internet-based survey on rectal douching practices. The survey was available in English, French, Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 41 publications
6
34
1
Order By: Relevance
“…Previous studies have demonstrated that douching practices by MSM are associated with an increased prevalence of STI like chlamydia,10 gonorrhoea,9 LGV8 11 and self-reported STI 3 4. Differences in the design of previous work and this study could explain the contrast between findings.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…Previous studies have demonstrated that douching practices by MSM are associated with an increased prevalence of STI like chlamydia,10 gonorrhoea,9 LGV8 11 and self-reported STI 3 4. Differences in the design of previous work and this study could explain the contrast between findings.…”
Section: Discussioncontrasting
confidence: 67%
“…In a Peruvian study among 824 MSM, 27% reported a history of rectal douching through a computer-assisted self-interview 2. In two large self-reported internet surveys, 35%–66% reported rectal douching 3 4. In these two surveys, MSM who used rectal douches were more often HIV positive, had more sex partners, had more CAS and more often identified as both receptive and insertive than those who did not use rectal douches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations